Essays in Criminal Law in Honour of Sir Gerald Gordon. - Chalmers, James; Leverick, Fiona; Farmer, Lindsay; Ashworth, Andrew; Clive, Eric M. (Edinburgh : Edinburgh University Press, 2010)
This collection of essays honours the work of Sir Gerald Gordon CBE QC LLD (1929-). In modern times few, if any, individuals can have been as important to a single country's criminal law as Sir Gerald has been to the criminal law of Scotland. His monumental work The Criminal Law of Scotland (1967) is the foundation of modern Scottish criminal law and is recognised internationally as a major contribution to academic work on the subject. Elsewhere, he has made significant contributions as an academic, judge and as a member of the Scottish Criminal Cases Review Commission. Reflecting the academic rigour and practical application of Sir Gerald's work, this volume includes essays on criminal law theory, substantive law and evidence and procedure by practitioners and academics within and outside of Scotland, including contributions from England, Ireland and the USA.
Intro -- Series -- Title -- Copyright -- Contents -- Preface -- Contributors -- Abbreviations -- Cases -- Foreword -- Sir Gerald Gordon -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Chapter 11 -- Chapter 12 -- Chapter 13 -- Chapter 14 -- Chapter 15 -- Chapter 16 -- Chapter 17 -- Chapter 18 -- Chapter 19 -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Criminal law -- Scotland; Electronic books